International Evidenceon Fiscal Solvency : Is Fiscal Policy "Responsible"? - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 2007)
This paper looks at fiscal solvency and public debt sustainability in both emerging market and advanced countries. Evidence of fiscal solvency, in the form of a robust positive conditional relationship between public debt and the primary fiscal balance, is established in both groups of countries. Evidence of fiscal solvency is much weaker, however, at high debt levels. These findings suggest that many industrial and emerging market economies, including several where fiscal solvency has been the subject of recent debates, appear to conduct fiscal policy responsibly. Yet our results cannot reject the hypothesis of fiscal insolvency in groups of countries with high debt ratios.